Perspectives on the Philosophy of Culture Husserl and Cassirer - Antonucci, Elio; Breyer, Thiemo; Cavallaro, Marco (Schriften zur Phänomenologie und Anthropologie, 2022)
The volume provides the first extensive analysis of Husserl's and Cassirer's approaches to the investigation of culture. It assembles contributions by leading international scholars and young researchers, offering an advanced comparison of the philosophies of culture in both thinkers.